Pharmacoeconomic study of antipsychotic drugs in India - Prasad, S. Nagaraja; H., Vedavathi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Schizophrenia is a disorder of relatively high point prevalence, low incidence and high disability. It accounts for nearly 1.5-3% of total national expenditure on health care. There is a gross variation in the cost of various branded and generic versions of antipsychotics available in India. This can lead to decreased patient compliance. The present study was undertaken to highlight this variation in the cost of various preparations of antipsychotics (branded and generic) available in India. Methods: Cost ratio and Percentage variation in cost of various antipsychotics available were calculated by standard formulae and analysed. Results: There is a very high variation in the cost of various antipsychotics available in India. The highest variation in cost ratio was seen with risperidone 2mg, 3mg and olanzapine 10mg, while the highest percentage cost variation was seen with risperidone 3mg, 4mg, 1mg; olanzapine 2.5mg, 5mg, 50mg, 100mg; levosulpiride 25mg and chlorpromazine 20mg. The lowest percentage cost variation was seen with Flupenthixol 3mg and Amisulpiride 300mg. Conclusions: There is a definite need to further strengthen the Drug Price Regulatory Mechanisms with regard to antipsychotics available in India in order to improve the patient compliance and thus cure rates of this burdensome and costly illness.